Efecto de la suplementación con tres niveles de betaína natural en época de verano sobre los índices productivos del pollo de carne cobb 500. - Reyna García, Brenda Nataly (2014)
This research was conducted in the poultry company Agropecuaria Santa Maria S.A.C., located in the district of Huanchaco, Trujillo Province, Department La Libertad; in the period between January and February 2013, to determine the effect of the inclusion of three levels of betaine in the diet on the performance of Cobb 500 chickens. A total of 192 male broilers were used in a completely randomized design, distributed in four treatments: T0 without betaine, T1 with 0,05, T2 with 0,10 and T3 with 0,15% of betaine respectively, in the growing and finishing stages. By statistical analysis, the final weights and increases in total weights of the treatments showed highly significant differences (p< 0,01), T3 and T2 treatments had the highest values, 2,79 and 2,75 kg and 2,77 and 2,73 kg respectively, being higher than T1 and T0 : 2,67 and 2,63 kg and 2,66 and 2,62 kg respectively. The feed intake was 4,95; 4.94; 4,84 and 4,85 kg for T3, T2, T1 and T0 respectively (p > 0,05). The addition of betaine at levels of 0,15 and 0,10 % improved feed conversion of chickens (1,80 and 1,81) and were significantly different at T0 and T1 (1,84 and 1,85) respectively (p < 0.01). Mortality rates of the treatments showed no significant differences (p > 0.05). The highest rates of productive efficiency were obtained by the T2 and T3 treatments (361, 3 and 356,7) and outperformed the T0 respectively 10,2 and 8,8 % respectively. Betaine levels at 0,15 and 0,10 % improved breast yield achieving levels of 22,50 and 22,48 % respectively and were statistically significant ( p <0,05 ) compared to T0 and T1. The treatment that received the highest benefit-cost ratio was T3 treatment, with a value of 1,29, followed by T2, with 1,28, and then treatment with 1,26 T0 and T1. It is concluded that the inclusion of betaine at levels of 0,15 % and 0,10 %, produced the best production rates of Cobb 500 broiler.